Characteristics of early-onset neonatal sepsis caused by Escherichia coli - Chin-Han Tsai; Yi-Yung Chen; Kuo-Gon Wang; Chen-Yu Chen; Chie-Pein Chen (Elsevier, 2012)
Objective: This study was conducted to document the perinatal risk factors associated with early-onset neonatal Escherichia coli sepsis and adverse neonatal outcomes. Materials and Methods: A case-control study of early-onset E coli sepsis compared with that of non-E coli sepsis was conducted by a retrospective data review of all infants with a diagnosis of sepsis during the first 7 days of life from the pediatric unit of Mackay Memorial Hospital from January 2004 to October 2008. After adjustment for gestational age, each patient with E coli early-onset sepsis was further compared with two gestational age-matched uninfected controls. Results: Compared with infants with non-E coli sepsis (n = 27), infants with E coli sepsis (n = 19) were more likely to have preterm birth, especially at less than 30 weeks of gestation (47% vs. 4%, p < 0.01), very low birth weights (<1500 g; 47% vs. 4%, p < 0.01), intrapartum fever (26% vs. 4%, p = 0.036), preterm premature rupture of membranes (PPROM; 74% vs. 11%, p < 0.01), prolonged rupture of membranes (>24 hours; 47% vs. 0%, p < 0.01), antibiotic use (63% vs. 15%, p < 0.01), and sepsis onset on the first day of life (63% vs. 15%, p < 0.01). After adjusting for gestational age, intrapartum fever (26% vs. 5%, p = 0.035) and PPROM (74% vs. 39%, p = 0.015) were more common in infants with E coli sepsis. Fifteen of the 19 E coli isolates (79%) were ampicillin-resistant, and three (16%) were gentamicin-resistant. Antepartum and intrapartum antibiotic exposure was associated with ampicillin-resistant E coli sepsis (100% vs. 43%, p < 0.01). Conclusion: Early-onset E coli sepsis is more common in premature and very low birth weight infants and is more likely associated with intrapartum fever, PPROM, and sepsis onset on the first day of life than non-E coli sepsis. Broad-spectrum, multiple antibiotics or longer duration of antibiotic exposure may be associated with antibiotic-resistant pathogen infection.